2015
DOI: 10.2298/vsp140622066m
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of soluble Fas plasma levels in patients with sepsis

Abstract: Our results suggest that initial sFas plasma levels in patients with sepsis correlated with the values of APACHE II score and separated very well the patients with septic shock versus the normotensive patients, the patients with and without MODS, and survivors versus nonsurvivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…23 Previous studies from Mikic et al, revealed that soluble Fas concentrations positively correlated with APACHE II scores (r=0.6046, p<0.001). 12 The weak correlation in our study was attributable to several possibilities, such as no uniformity in our study subjects'length of illness before soluble Fas levels were measured, or by factors of flaws in APACHE II score assessments. Soluble Fas levels in this study were indeed measured on the first-day sepsis was diagnosed by a physician, but durations of illness before the subjects came to the Dr. Soetomo Hospital's emergency room were varied.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…23 Previous studies from Mikic et al, revealed that soluble Fas concentrations positively correlated with APACHE II scores (r=0.6046, p<0.001). 12 The weak correlation in our study was attributable to several possibilities, such as no uniformity in our study subjects'length of illness before soluble Fas levels were measured, or by factors of flaws in APACHE II score assessments. Soluble Fas levels in this study were indeed measured on the first-day sepsis was diagnosed by a physician, but durations of illness before the subjects came to the Dr. Soetomo Hospital's emergency room were varied.…”
Section: Resultsmentioning
confidence: 66%
“…Fas receptor (CD95/ APO-1) is the central molecule involved in apoptosis in sepsis. 11,12 Sepsis causes the level of proinflammatory cytokines and Fas receptor (Fas rec) to increase and the level of elevation is correlated with disease severity. Increasing level of soluble Fas will follow increasing level of Fas receptor.…”
Section: Introductionmentioning
confidence: 99%